Weaning stress and intestinal health of piglets: A review - Tang, Xiaopeng; Xiong, Kangning; Fang, Rejun; Li, Meijun (Frontiers in Immunology, 2022)
Weaning is considered to be one of the most critical periods in pig production, which is related to the economic benefits of pig farms. However, in actual production, many piglets suffer from weaning stress due to sudden separation from the sow, changes in diets and living environment, and other social challenges. Weaning stress often causes changes in the morphology and function of the small intestine of piglets, disturbs digestion and absorption capacity, destroys intestinal barrier function, and ultimately leads to reduced feed intake, increased diarrhea rate, and growth retardation. Therefore, correctly understanding the effects of weaning stress on intestinal health has important guiding significance for nutritional regulation of intestinal injury caused by weaning stress. In this review we reviewed the effects of weaning stress on intestinal health of piglets, from the aspects of intestinal development, and intestinal barrier function, thereby providing a theoretical basis for nutritional strategies to alleviate weaning stress in mammals in future studies.